Religious Sphere dan Pergeseran Budaya: Analisis Konseptual dan Sosiologis dalam Masyarakat Modern - Kadir, Arianto; Grace M.A. Dengah; Melki Kumaat; Syafaruddin; Ferri Sangiang (Fakultas Pertanian, 2024)
This study aims to identify and analyze the concept of religious sphere in the context of cultural shifts in modern society. The study was conducted using a qualitative approach through a literature study method on theories of the sociology of religion and the dynamics of contemporary cultural change. The results of the study show that the religious sphere is no longer limited to the realm of worship, but has penetrated public spaces such as social media, educational institutions, and state policies. This shift forms a transformation of collective identity, strengthens religiosity while giving rise to fragmentation of religious meaning due to the influence of popular culture and the commercialization of religious symbols. This study emphasizes the importance of reformulating the understanding of the religious sphere so that it remains relevant in shaping social and cultural ethics in the midst of modernity, without losing its substantial values. The religious sphere remains a strategic field in shaping the direction of civilization, as long as it is able to adapt to the changing times.